Calculation of Motor Excitation Force Caused by Torque Pulsation - SATO, Taichi; NAGAHASHI, Katsuaki; OKAMOTO, Joji; NAGAI, Makoto; OTA, Hiroki (Transactions of the Japan Society of Mechanical Engineers Series C, 2004)
The excitation force of an induction motor is composed of many peak frequency components. The highest peak of the force appears at a frequency of 100 Hz, which is twice the power-supply frequency. We called this frequency component an “2 f component”, and analyzed the force of this 2 f component. When the motor is in operation, the torque of the motor fluctuates at twice the power-supply frequency. This torque pulsation is cause of the excitation force of the 2 f component. Based on the mechanism of excitation-force generation, we developed a method for estimating the excitation force of a motor. Using this method, the excitation force of the motor was estimated from both the equivalent circuit and finite-element model of the motor. The results obtained by this method agreed well with the results of the excitation force measured by using load cell.